Analisis Kepuasan Pengguna Terhadap Penerapan Aplikasi Layanan GOFOOD Menggunakan Metode PIECES Framework - Dina Evitria; Joy Nashar Utamajaya; Adi Hermawansyah (STMIK Budi Darma, 2022)
The progress of the times, many business entrepreneurs are starting to open up opportunities in the service sector. The company also takes advantage of advances in information technology to provide convenience for customers. There are startups in the service sector, for example Gojek. The startup also provides a feature for food delivery services, namely Gofood, which is available on Gojek. This study aims to determine the factors that influence customer satisfaction with the Go-jek application for Go-food services. The model used to explain user satisfaction with the implementation of Go-food services is the PIECES method (performance, information, economy, control, efficiency, service). This study uses descriptive quantitative data, Likert scale, performance, information, economy, control and service, efficiency, and service. As a system analysis tool, PIECES pays special attention to detailed and comprehensive systems, identifies system strengths and weaknesses, and uses them as a reference for further enterprise development. The average result of the satisfaction of gofood service users has reached a value of 4.4. This means that users are SATISFIED with gofood services.